2013
DOI: 10.1096/fj.12-224352
|View full text |Cite
|
Sign up to set email alerts
|

The Arp2/3 complex mediates multigeneration dendritic protrusions for efficient 3‐dimensional cancer cell migration

Abstract: Arp2/3 is a protein complex that nucleates actin filament assembly in the lamellipodium in adherent cells crawling on planar 2-dimensional (2D) substrates. However, in physiopathological situations, cell migration typically occurs within a 3-dimensional (3D) environment, and little is known about the role of Arp2/3 and associated proteins in 3D cell migration. Using time resolved live-cell imaging and HT1080, a fibrosarcoma cell line commonly used to study cell migration, we find that the Arp2/3 complex and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 45 publications
(51 reference statements)
3
77
0
Order By: Relevance
“…2 A ), cells embedded in 3D matrix displayed highly branched dendritic protrusions (Fig. 2 B , J ) [see also Giri et al (5)]. These branched protrusions contained both microtubules and F-actin (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…2 A ), cells embedded in 3D matrix displayed highly branched dendritic protrusions (Fig. 2 B , J ) [see also Giri et al (5)]. These branched protrusions contained both microtubules and F-actin (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Recent studies have shown a strong correlation between 3D cell migration speed and protrusion activity, defined here as the number of protrusions generated per unit time, not the length or lifetime of protrusions (5, 11, 12). Therefore, we hypothesized and verified that pharmacological manipulation of microtubules using nocodazole and taxol would reduce protrusion activity because these treatments reduce cell speed in 3D matrices (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the last two decades, lamellipodial-driven migration has been predominately investigated on flat two-dimensional (2-D) substrates. However, recent studies have pointed out that several aspects of cell motility significantly differ in a three dimensional microenvironment (Wu et al, 2014;Mierke et al, 2010;Giri et al, 2013). In summary, the basic mechanical concept of the lamellipodia-dependent migration is that the actin polymerization induces the protrusion formation of the membrane in the direction of the migration.…”
Section: Introductionmentioning
confidence: 99%
“…However, cell migration in vivo often forces cells to remodel, exert pulling forces on, and move through a 3D collagen I-rich matrix. Recent work has demonstrated that mechanisms of 3D migration are often different from their 2D counterparts (9)(10)(11)(12)(13)(14)(15). Migration on 2D dishes, which induces a basal-apical polarization of the cell, is driven by actomyosin contractility of stress fibers between large focal adhesions and the formation of a wide lamellipodium terminated by thin filopodial protrusions at the leading cellular edge (4,16).…”
mentioning
confidence: 99%
“…The same cells in collagen-rich 3D matrix do not display a lamellipodium or filopodia. Instead, they display highly dendritic pseudopodial protrusions controlled by distinct proteins that rely both on acto-myosin contractility and microtubule assembly/disassembly dynamics (11,17). 3D cell migration depends on the expression of metalloproteinases (MMPs), which are dispensable in 2D migration, and physical properties of the 3D matrix (18), such as pore size (6).…”
mentioning
confidence: 99%